Control and simulation design of a cascaded single-phase VIENNA switching converter based on small signal modeling - Wang Cong; Hu Haoyu; Cheng Hong (矿业科学学报, 2020)
In order to avoid using the heavy and expensive line frequency transformer in the traditional high-voltage mining AC driver, and considering that the mining fan does not need energy feedback, a three-phase rectifier consisting of three star connected cascaded single-phase VIENNA switching converter (CSVSC) is proposed, which can be used as rectifier stage of the AC driver.The CSVSC has the characteristics of one-way flow of energy and fewer switching devices, which can effectively reduce the withstand voltage of the switching device and diode.Therefore, the CSVSC can be applied to high-voltage and high-power applications, eliminating the line frequency transformer and reducing the cost of the AC driver.Small-signal modeling is of great significance for studying the dynamic process of circuits.In this paper, the small-signal model is established by analyzing the working state of the CSVSC.The transfer function of the compensation network is designed according to the given parameters.The correctness of the proposed small-signal model is proved by Bode diagram and simulation.